Ca2+‐regulated and diurnal rhythm‐regulated Na+/Ca2+ exchanger AtNCL affects flowering time and auxin signalling in Arabidopsis. (9th November 2015) - Li, Penghui; Zhang, Gaoyang; Gonzales, Naomi; Guo, Yingqing; Hu, Honghong; Park, Sunghun; Zhao, Jian
Abstract: Calcium (Ca 2+ ) is vital for plant growth, development, hormone response and adaptation to environmental stresses, yet the mechanisms regulating plant cytosolic Ca 2+ homeostasis are not fully understood. Here, we characterize an Arabidopsis Ca 2+ ‐regulated Na + /Ca 2+ exchanger AtNCL that regulates Ca 2+ and multiple physiological processes. AtNCL was localized to the tonoplast in yeast and plant cells. AtNCL appeared to mediate sodium (Na + ) vacuolar sequestration and meanwhile Ca 2+ release. The EF‐hand domains within AtNCL regulated Ca 2+ binding and transport of Ca 2+ and Na + . Plants with diminished AtNCL expression were more tolerant to high CaCl2 but more sensitive to both NaCl and auxin; heightened expression of AtNCL rendered plants more sensitive to CaCl2 but tolerant to NaCl. AtNCL expression appeared to be regulated by the diurnal rhythm and suppressed by auxin. DR5 :: GUS expression and root responses to auxin were altered in AtNCL mutants. The auxin‐induced suppression of AtNCL was attenuated in SLR / IAA14 and ARF6 / 8 mutants. The mutants with altered AtNCL expression also altered flowering time and FT and CO expression; FT may mediate AtNCL‐regulated flowering time change. Therefore, AtNCL is a vacuolar Ca 2+ ‐regulated Na + /Ca 2+ exchanger that regulates auxin responses and flowering time. Abstract : AtNCL is a vacuolar Na + /Ca 2+ exchanger with EF hands that mediates sodium (Na + ) vacuolar sequestration and meanwhile Ca 2+ release. The Ca 2+ /Na + exchanger activity can be regulated by Ca 2+ and camodulin. AtNCL expression in Arabidopsis is regulated by diurnal rhythm and suppressed by auxin. Its mutants showed altered flowering time and auxin responses. Therefore, AtNCL is a Ca 2+ ‐regulated vacuolar Na + /Ca 2+ exchanger that regulates auxin responses and flowering time.